Managing subject guides with SQL Server and ASP.Net - Greene, Araby (Library hi tech, 2008)
Purpose - The purpose of this paper is to report on the content management solution for 50 subject guides maintained by librarian subject specialists at the University of Nevada, Reno Libraries.Design methodology approach - The Web Development Librarian designed an SQL Server database to store subject guide content and wrote ASP.Net scripts to generate dynamic web pages. Subject specialists provided input throughout the process. Hands-on workshops were held the summer before the new guides were launched.Findings - The new method has successfully produced consistent but individually customized subject guides while greatly reducing maintenance time. Simple reports reveal the association between guides and licensed resources. Using the system to create course-specific guides would be a useful follow-up project. Skills learned in training workshops should be refreshed at regular intervals to boost confidence and introduce changes in the system.Practical implications - The advantages of centralizing content and separating it from presentation cannot be overstated. More consistency and less maintenance is just the beginning. Once accomplished, a library can incorporate Web 2.0 features into the application by repurposing the data or modifying the ASP.Net template. The now-organized data is clean and ready to migrate to web services or next-generation research guides when the time is right.Originality value - This paper uniquely reports on an SQL Server, ASP.Net solution for managing subject guides. SQL Server includes data management features that increase application security and ASP.Net offers built-in functionality for manipulating and presenting data. Utmost attention was given to creating simple user interfaces that enable subject specialists to create complex web pages without coding HTML.